"Who Were You?": Temporality and Intergenerational Empathy in Community Girlhood Studies. Issue 3 (1st December 2022) - Winstanley, Sarah; Bernier, Alexe
Abstract: While Girlhood Studies is an emerging field of academic study, knowledge about how to work with girls in the community has long been evolving. As community social workers doing critical, gender-transformative work with girls, we trained adult women volunteers in gender-specific girls' programs. Pedagogically rooted in popular education, our training approach, in drawing on volunteers' own memories of girlhood, evoked a diversity of stories, lived experiences, and understandings of how their lives were affected by systemic forces. In this article, we illustrate how explicating the temporality of girlhood with women can facilitate the interrogation of their own internalized sexism and adultism, and how building intergenerational empathy serves as a tool for reshaping adult women's ability to work collaboratively with and build relationships with girls.